DOMINASI TOKOH AGAMA DAN TOKOH BLATIR DI PESTA DEMOKRASI DI DESA BATOKABAN - Rizqi Yanto; Dian Eka Indriani (STKIP Pesisir Selatan, 2026)
The implementation of democracy in rural areas does not occur in a social vacuum free from external influences. In many villages across Madura, including Batokaban Village, Konang District, Bangkalan Regency, electoral processes are, in reality, shaped by forces operating beyond the formal institutions of the state. This study aims to examine how religious leaders and blater figures establish and exercise their dominance during every democratic electoral event, as well as to analyze the patterns of relationships between these two actors, whether cooperative, competitive, or alternating between the two.This study employs a descriptive qualitative approach. Data were collected through in-depth interviews, passive participant observation, and document analysis. Informants were selected purposively and included religious leaders, blater figures, village officials, and community members as voters. Data were analyzed using the interactive model developed by Matthew B. Miles and A. Michael Huberman, while data validity was ensured through source, technique, and time triangulation.The findings reveal that religious leaders utilize their moral authority and religious networks to shape citizens' political preferences, whereas blater figures rely on social networks, their capacity to mobilize supporters, and the provision of material benefits to cultivate political loyalty. These two actors frequently operate in a complementary and synergistic relationship: religious leaders provide moral legitimacy, while blater figures ensure that such support is translated into concrete political outcomes on the ground.